School-based Factors Explaining Poor Academic Performance of Primary School Pupils in Lushoto District, Tanzania - Kahangwa, George Kahangwa; Kafanabo, Eugenia Kafanabo (Papers in Education and Development, 2023)
Abstract A study was undertaken to establish why several primary schools in Lushoto district, in Tanzania were experiencing poorest academic performance across years in the country. Literature was yet to empirically establish the issues which could explain what was transpiring in the schools. Therefore, it was important to undertake explanatory mixed methods research that involved administering questionnaires to heads of schools, reviewing pupils ' records, interviewing Ward Educational Officers, and holding discussions with selected teachers. The study found out that poor academic performance among Lushoto primary schools is due to weak school leadership, imbalanced allocation of teachers, poor management of learning time and inadequate infrastructure. It is recommended, among others, that education managers in Lushoto should take measures which target improvement around each factor. Keywords: primary education, school leadership, school infrastructure, Tanzania.